(3JMaI GdYLGFH hWQaI GdZQGFHs - (3GHf GdGKjQ , ESeGYjd Hf CMeO Hf SYjO GdMdHj GdTGaYj, YeGO GdOjf,J (B699 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH jfUQa ajg GdfGXQ s
(3BNQgG (B:s
(3MLQ RHO GdHMQhEPG Ydb Ydi GdeWdbI hVYJ s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B309 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B259s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B369s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs